Do tarantulas have teeth? : questions and answers about poisonous creatures - Berger, Melvin; Berger, Gilda; Effler, James M., 1956- (New York, N.Y. : Scholastic Reference, 1999)
Provides answers to a variety of questions about various poisonous creatures, such as "Do Gila monsters bite humans," "What are killer bees," "Which ant sting hurts the most," and "Are frogs poisonous?"
Includes index.
G5
Keywords: Poisonous animals -- Miscellanea -- Juvenile literature; Poisonous animals -- Miscellanea; Questions and answers